EFEKTIVITAS PENERIMAAN PBB DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN PURWOREJO JAWA TENGAH - Mursyid Mursyid (LPPM Akademi Manajemen Administrasi Yogyakarta, 2021)
The purpose of this study was to determine the effectiveness and contribution of PBB revenue to PAD in Purworejo Regency, Central Java. The results of the research and discussion concluded that 1) The realization of PBB revenue in Purworejo Regency for the last 5 years was still above 100%. Thus, during that period, PBB revenue was categorized as “Very Effective” and 2) The contribution given by PBB to PAD in Purworejo Regency during the last 5 years was categorized as very low, because all of them were still below 10%.